The effectiveness of mindfulness-based interventions for children with autism and their parents: a systematic review and meta-analysis - Qiyan Peng; Yujie Dong; Jie Jin; Huan Ao; Chi Zhang; Yanfei Ma (Frontiers in Psychology)
ObjectiveThis study aims to systematically evaluate the efficacy of mindfulness-based interventions (MBIs) for children diagnosed with autism spectrum disorder (ASD) and their parents.MethodsA comprehensive search of PubMed, Embase, Cochrane Library, Web of Science, PsycINFO and ERIC was conducted to identify randomized controlled trials (RCTs) published up to December 31, 2024, that assessed the effects of MBIs on children with ASD and their parents. Two independent reviewers screened studies, extracted relevant data, and assessed the quality of the included literature. A meta-analysis was performed using standardized mean differences (SMDs) and 95% confidence intervals (CIs).ResultsA total of 12 RCTs involving 643 participants were included. The meta-analysis showed that MBIs significantly reduced parental stress [SMD = −0.69, 95% CI (−1.36, −0.02), p = 0.04], improved parental mindfulness awareness [SMD = 3.08, 95% CI (0.26, 5.90), p = 0.03], and alleviated anxiety, depression, and stress in parents [SMD = −0.57, 95% CI (−1.09, −0.06), p = 0.03]. Additionally, MBIs significantly improved social responsiveness in children with autism [SMD = −0.35, 95% CI (−0.66, −0.04), p = 0.03]. However, no statistically significant differences were observed between the MBI and control groups in reducing problematic behaviors in children [SMD = −0.45, 95% CI (−0.90, 0.00), p = 0.05], improving children’s emotional and behavioral difficulties [SMD = −0.23, 95% CI (−0.66, 0.19), p = 0.28], or enhancing parental psychological resilience [SMD = 0.85, 95% CI (−1.96, 3.66), p = 0.55].ConclusionThis meta-analysis demonstrates that MBIs significantly reduce parental stress, alleviate anxiety, depression, and stress, and enhance mindfulness awareness in parents of children with autism. Furthermore, MBIs were found to significantly improve social responsiveness in children with autism. However, their effects on children’s emotional and behavioral challenges and parental psychological resilience remain inconclusive.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023424059.